DOES TITANIUM ELASTIC NAIL (TEN) FOR FEMUR SHAFT FRACTURE IN CHILDREN HAVE SUPERIOR FUNCTIONAL OUTCOMES THAN SPICA CAST APPLICATION? AN EXPERIENCE FROM TERTIARY CARE HOSPITAL - SIDDIQ , MZ; BAQER, DR; UMAIR , M; RAZZAQUE , MA; SHAFIQ , M (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to compare functional outcomes in children with femur shaft fractures treated with ether titanium elastic nail or spica cast application. This prospective cohort study was conducted at the Department of Orthopedic and Spine, Aziz Bhatti Shaheed Teaching Hospital, Gujrat, from 1st June 2020 to 31st December 2022. This study involved 60 children of both genders, aged 3-6 years, presenting with femoral shaft fractures (Winquist I & II), randomly allocated into two groups for treatment. Patients in Group E were treated with titanium elastic nails, while a hip spica cast was applied to patients in Group S. Functional outcome was measured with the meantime to walk independently, which was noted and compared between the two groups. Patients had a mean age of 4.42±1.12 years, while the mean weight was 18.23±2.09 Kg. There were 21 (35.0%) female and 39 (65.0%) male patients with a male-to-female ratio of 1.9:1. The mean time to walk independently was significantly shorter in children treated with titanium elastic nail as compared to hip spica cast (5.60±1.28 vs. 8.93±1.98 weeks; p<0.001). A similar significant difference was observed between groups across various subgroups of patients based on age, gender, and weight. We concluded that internal fixation of pediatric femoral shaft fractures utilizing titanium elastic nail had superior functional outcomes as compared to hip spice cast application in terms of significantly shorter mean time to walk independently along with the minimally invasive nature of the procedure and better patient hygiene and cosmesis advocate preferred use of titanium elastic nails for management of such fractures.